2017
DOI: 10.7717/peerj.3889
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of microbial community diversity estimated by closed- and open-reference OTUs

Abstract: Next-generation sequencing of 16S ribosomal RNA is widely used to survey microbial communities. Sequences are typically assigned to Operational Taxonomic Units (OTUs). Closed- and open-reference OTU assignment matches reads to a reference database at 97% identity (closed), then clusters unmatched reads using a de novo method (open). Implementations of these methods in the QIIME package were tested on several mock community datasets with 20 strains using different sequencing technologies and primers. Richness (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
113
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(122 citation statements)
references
References 31 publications
4
113
0
Order By: Relevance
“…ting due to open reference OTU clustering (Edgar, 2017), we ran the same PERMANOVA model on the bacterial Unifrac distance matrix.…”
Section: Discussionmentioning
confidence: 99%
“…ting due to open reference OTU clustering (Edgar, 2017), we ran the same PERMANOVA model on the bacterial Unifrac distance matrix.…”
Section: Discussionmentioning
confidence: 99%
“…Metabarcoding has become the most popular method to "scale up" ecological studies related to biodiversity (Porter & Hajibabaei, 2018), especially for microscopic organisms (Bucklin et al, 2016;Yu et al, 2012). The clustering strategy for the generation of OTU, a critical technical point in metabarcoding analysis, has been highly discussed and updated (Amir et al, 2017;Callahan et al, 2016;Edgar, 2016Edgar, , 2017). Here, we tested effects of different clustering scenarios on inferring community-environment interactions in multiple aspects.…”
Section: Discussionmentioning
confidence: 99%
“…To account for these factors, a typical first step of microbiome analysis is to resolve the data into Operational Taxonomic Units (OTUs), or clusters of sequences with 97% or greater similarity. There are many methods for identifying OTUs [2], roughly classifiable into closed-reference methods, which use a reference database of known organisms, or de novo methods.However, when applied to mock communities, it is widely found that both types of methods cannot accurately identify true OTUs in a sample [3,4,5,6,7,8].OTUs are problematic entities, lacking both biological and physical interpretability. They only roughly correspond to biological species, genera or higher taxonomic entities, and they do not correspond to true, error-free sequences in the sample.…”
mentioning
confidence: 99%
“…However, when applied to mock communities, it is widely found that both types of methods cannot accurately identify true OTUs in a sample [3,4,5,6,7,8].…”
mentioning
confidence: 99%